2016
DOI: 10.1149/ma2016-02/1/135
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cycle Stability of Lithium Iron Phosphate in Aqueous Electrolytes By Increasing Electrolyte Molarity

Abstract: The development of an aqueous lithium ion battery (ALIB) has the potential to greatly improve the safety and lower the cost of lithium ion battery storage systems, while safeguarding the environment. The problem of thermal runaway and ignition of a flammable electrolyte is absent. Aqueous electrolytes exhibit higher ionic conductivities than their organic counterparts [1], allowing for the use thicker electrodes without suffering mass transport limitations. Combined, this promises to allow for a significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This increased solvation free energy implies an increased difficulty for the chemical and electrochemical dissolution of Na 2 Zn 3 [Fe(CN) 6 ] 2 when using a concentrated 17 m NaClO 4 electrolyte. 25,28 In addition, we performed an in situ XRD study of Na 2 Zn 3 [Fe(CN) 6 ] 2 electrodes to investigate and determine the structural changes during cycling in 1 and 17 m NaClO 4 electrolyte. When 1 m NaClO 4 was used as electrolyte (Figure 4a and Figure S6), a new cubic phase 20 with 2θ values of 17.10°, 24.26°, 34.60°, and 38.83°attributed to Zn 3 [Fe-(CN) 6 ] 2 was observed during Na-ion extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased solvation free energy implies an increased difficulty for the chemical and electrochemical dissolution of Na 2 Zn 3 [Fe(CN) 6 ] 2 when using a concentrated 17 m NaClO 4 electrolyte. 25,28 In addition, we performed an in situ XRD study of Na 2 Zn 3 [Fe(CN) 6 ] 2 electrodes to investigate and determine the structural changes during cycling in 1 and 17 m NaClO 4 electrolyte. When 1 m NaClO 4 was used as electrolyte (Figure 4a and Figure S6), a new cubic phase 20 with 2θ values of 17.10°, 24.26°, 34.60°, and 38.83°attributed to Zn 3 [Fe-(CN) 6 ] 2 was observed during Na-ion extraction.…”
Section: Resultsmentioning
confidence: 99%
“…20 Using highly concentrated electrolytes appears to be a facile and efficient way to extend the electrochemical stability window of aqueous electrolyte 4,11,21−24 and suppress the electrochemical dissolution of electrode-active materials. 17,25,26 For example, Suo et al 11 first reported a wide stability window of >2.5 V for an aqueous electrolyte solution by use of 9.26 m sodium trifluoromethanesulfonate (NaOTF) electrolyte. Very recently, Nakamoto et al 12,17 revealed that increasing the salt concentration of NaClO 4 aqueous solutions can effectively reduce the electrochemical corrosion of Na 2 MnFe(CN) 6 due to a common-ion effect, which restricts the dissolution of MnFe(CN) 6 2− anions into the aqueous electrolyte and therefore dramatically enhances the cycling stability of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Cycling degraded cells at an elevated temperature should accelerate ionic transport without significantly effecting electrical transport, and thus help to differentiate electrical and ionic degradation mechanisms. 34,35 Figure 6 shows how none of the cells recovered any significant portion of their capacity when cycled afterward at 60 °C. This points to the loss of electrical contact between particles, whether via volume change from lithiation/delithiation of P and/or from large SEI growth that induces electrical isolation of the active material.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…Yushin et al also reported stable charge−discharge cycling of LiFePO 4 electrodes by increasing Li salt molarity in aqueous electrolytes. 18 Despite the facile approach, there is a complex rational mechanism behind the successful demonstration of moderately high voltage ARLBs with molten salt hydrate electrolytes. A high concentration of Li + ions significantly reduces the activity of uncoordinated water, leading to the enhanced oxidative stability of the electrolyte.…”
Section: ■ Introductionmentioning
confidence: 99%